2022
DOI: 10.1093/mnras/stac2474
|View full text |Cite
|
Sign up to set email alerts
|

The formation of clusters and OB associations in different density spiral arm environments

Abstract: We present simulations of the formation and evolution of clusters in spiral arms. The simulations follow two different spiral arm regions, and the total gas mass is varied to produce a range of different mass clusters. We find that including photoionizing feedback produces the observed cluster mass radius relation, increasing the radii of clusters compared to without feedback. Supernovae have little impact on cluster properties. We find that in our high density, high gas mass simulations, star formation is les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 97 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…They can be driven by the complex interplay between gravity and stellar feedback effects, and the thermodynamic response of the multi-phase ISM. In galaxy-wide simulations 45 spiral density waves lead to high-velocity collisions of flows that can form massive OB clusters such as the ones seen in Cygnus X. In any case, our finding will have major ramifications for our understanding of molecular cloud assemblage in the Milky Way and other galaxies.…”
Section: Discussionmentioning
confidence: 74%
“…They can be driven by the complex interplay between gravity and stellar feedback effects, and the thermodynamic response of the multi-phase ISM. In galaxy-wide simulations 45 spiral density waves lead to high-velocity collisions of flows that can form massive OB clusters such as the ones seen in Cygnus X. In any case, our finding will have major ramifications for our understanding of molecular cloud assemblage in the Milky Way and other galaxies.…”
Section: Discussionmentioning
confidence: 74%
“…They can be driven by the complex interplay between gravity and stellar feedback effects, and the thermodynamic response of the multi-phase interstellar medium. In galaxy-wide simulations [45] spiral density waves lead to high-velocity collisions of flows that can form massive OB clusters such as the ones seen in Cygnus X. In any case, our finding will have major ramifications for our understanding of molecular cloud assemblage in the Milky Way and other galaxies.…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, 3D dust mapping and observations of young stellar objects (YSOs) in the Local Bubble have shown that energy from multiple supernovae can create a shell of molecular gas, fueling subsequent star formation (Zucker et al 2022). At the moment, it is unclear which of these two opposing effects dominates star formation rates on a galactic scale; however, studies using simulations seem to show that the effects of stellar feedback might be dependent on the density of the local ISM around stars (Gatto et al 2015;Dobbs et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While simulations have given us the mechanism to understand how various forms of feedback interact with the ISM on small scales (Peters et al 2011;Dale et al 2014;Chen et al 2015;Geen et al 2015;Choi et al 2017;, it is still difficult to model the effects of feedback across entire galaxies (Girichidis et al 2016;Dobbs et al 2022). Modeling feedback in detail requires subparsec-scale resolution (e.g., TIGRESS; , making it difficult to propagate the effects to the kiloparsec scales of galaxies (e.g., FIRE; Hopkins et al 2014).…”
Section: Introductionmentioning
confidence: 99%